INDUKSI AKAR STEK BATANG TANAMAN NILAM MENGGUNAKAN ZPT IBA PADA BEBERAPA KOMPOSISI MEDIA TANAM - Yamin, Rahadian; Aji, Irwan Mahakam Lesmono; Idris, Muhamad Husni (Jurusan Kehutanan, 2021)
Patchouli (Pogostemon cablin Benth.) plant is one of the essential oil producing plants, that is useful in the chemical industry as a raw material for fragrance products and in the pharmaceutical field. The success rate of patchouli early growth, is largely determined by the cultivation techniques used, including the use of growth regulators, and growing media. This study aims to determine the effect of IBA growth regulators and the composition of plant media on the growth of patchouli plants. This research is carried out in the Greenhouse of the Forestry Study Program of the University of Mataram, using a Factorial Completely Randomized Design (RALF), the first factor is IBA growth regulator with 3 levels, namely 0, 20, 25 ppm and the second factor is composition of plant media with 3 levels, namely forest soil media, soil media:sand:compost (1:1:1), and soil media:sand:compost (2:1:3). The results show that the effect of IBA significantly affect the success percentage of cuttings and the number of roots of patchouli plants. The effect of plant media composition and the interaction between treatment of IBA with plant media composition did not have a significant effect on the growth parameters of patchouli plants.